Sprinting kinematics of athletes with selected physical disabilities - Andrews, B. S. (2014)
The purpose of this research was to gain insight into the sprinting of athletes with selected physical disabilities. The sprint performances of four Paralympic athletes (T43, T13, T37 and T38 classifications) were analysed in terms of variability in the biomechanics of their set position and in the kinematics of the initial acceleration phase and the maximal acceleration phase of their 100m sprints. The athletes also reported their perceptions about the potential of a rhythm training programme to influence their sprinting. A case study approach was used. Sprint kinematics were video-recorded four times over the training year. DartFish ProSuite software supported the digital tagging of anatomical landmarks and the calculation of the biomechanical features of the set position as well as the kinematics of each athlete. A subjective log was used to gather their perceptions about the rhythm training programme. There was variability in all aspects for all four Paralympic athletes. This should encourage coaches to help athletes find optimal kinematics in relation to their disability, rather than trying to coach them to a set template of an ideal form. Based on the kinematic data collected over all four test sessions, it appears that a coaching focus on stride length was the key to faster sprinting for this T43 (amputee) athlete. A coaching focus on stride frequency (once optimal stride length had been discovered) was the key for the T13 sprinter (visually impaired), and a coaching focus on stride frequency was the key to faster sprinting for both the T37 and T38 athletes (cerebral palsy). Although all of the athletes enjoyed the rhythm training programme, only the least experienced athlete (T38) reported that he would like to continue with this form of training.